(untitled) (Texas Journal of Medical Science, 2025)
This article examines the strategies and methods for preventing growth and development retardation in infants born with intrauterine growth restriction (IUGR) during their first year of life. IUGR is a significant perinatal complication that affects a child’s physical and cognitive development, potentially leading to long-term health consequences. The research highlights the importance of early identification, monitoring, and intervention to mitigate the negative effects of restricted intrauterine growth.